Nanotechnology between the lab and the shop floor: what are the effects on labor? - Invernizzi, Noela (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2011)
Nanotechnology’s effects on labor and employment have received little attention within research and debates on the social implications of nanotechnology. This article shows that, in spite of its incipient development, nanotechnology is unquestionably moving toward manufacturing, involving a still very small but increasing component of the labor force. Based on secondary data and the literature review, I compose a picture of the emerging jobs in nanotechnology and highlight four emerging trends in nanotechnology workers’ skills requirements. I show that, in addition to job creation, nanotechnology diffusion is likely to pose labor market changes that may be disruptive for some categories of workers.